GABAergic function in the lateral hypothalamus regulates feeding behavior: Possible mediation via orexin. Issue 4 (16th October 2019) - Yonemochi, Naomi; Ardianto, Chrismawan; Ueda, Daiki; Kamei, Junzo; Ikeda, Hiroko
Abstract: Aim: The lateral hypothalamus (LH) is known as the hunger center, but the mechanisms through which the LH regulates food intake are unclear. Since GABA neurons are reported to project to the LH, the present study investigated the role of GABAergic function in the LH in the regulation of feeding behavior. Methods: GABA levels in the LH were measured by in vivo microdialysis. Food intake after drug injection into the LH was measured every 1 hour for 4 hours. The mRNA levels were measured using RT‐PCR. Results: Food intake significantly increased GABA levels in the LH, suggesting that food intake stimulates GABAergic function in the LH. Injection of the GABAA receptor agonist muscimol into the LH significantly inhibited food intake, whereas injection of the GABAA receptor antagonist bicuculline into the LH did not significantly affect food intake. The inhibitory effect of muscimol injected into the LH was blocked by co‐administration of bicuculline. These results indicate that the stimulation of GABAA receptors in the LH inhibits food intake. We next examined whether the stimulation of GABAA receptors affects hypothalamic neuropeptides that are known to regulate feeding behavior. The injection of muscimol significantly decreased preproorexin mRNA in the hypothalamus. Conclusion: These results indicate that food intake activates GABAergic function in the LH, which terminates feeding behavior by stimulating GABAA receptors. Moreover, it is suggested that the stimulation of GABAA receptors in the LH reduces food intake through inhibition of orexin neurons. Abstract : We investigated whether GABAergic function in the lateral hypothalamus (LH) regulates feeding behavior. We showed that food intake increased GABA levels in the LH in in vivo microdialysis and that the GABAA receptor agonist muscimol injected into the LH decreased food intake. These results suggest that food intake activates GABA neurons projecting to the LH, and it terminates feeding behavior through GABAA receptors.